(untitled) (Research, Society and Development, 2021)
Objective: To evaluate patients diagnosed with Type 2 Diabetes Mellitus and Systemic Arterial Hypertension in a Family Health Strategy (FHS) located in the rural area of the municipality of Santa Bárbara do Pará, State of Pará, Brazil. Methodology: This is an epidemiological, observational, cross-sectional and descriptive study. The studied population consisted of patients with SAH and / or DM II, assisted in the referred FHS, within a period of 1 year. Results: 102 people participated in the study. Of these, 70 patients were hypertensive, 10 were diabetic and 22 had SAH and DM II, concomitantly. The female gender was predominant with 57.84% of cases. The most prevalent ethnic group was brown (43.13%). The study identified low adherence to the recommended diet, both in hypertensive patients (21.42%) and diabetics (30%) and in patients with both pathologies (45.45%). The rate of adherence to regular physical activity was also low in the 3 groups of the present study. Most (59.37%) of diabetics had glycemic levels above the recommended. The majority (66.3%) of hypertensive patients also had blood pressure levels above the appropriate level. Conclusion: Thus, it is imperative that there is a strengthening of the bond between the multidisciplinary health team and the patient assisted in the FHS, always seeking to exercise health care in a holistic way, in order to improve adherence to the treatment of SAH and DM II.